2022
DOI: 10.3390/ijms231810722
|View full text |Cite
|
Sign up to set email alerts
|

Novel Anti-Neuroinflammatory Properties of a Thiosemicarbazone–Pyridylhydrazone Copper(II) Complex

Abstract: Neuroinflammation has a major role in several brain disorders including Alzheimer’s disease (AD), yet at present there are no effective anti-neuroinflammatory therapeutics available. Copper(II) complexes of bis(thiosemicarbazones) (CuII(gtsm) and CuII(atsm)) have broad therapeutic actions in preclinical models of neurodegeneration, with CuII(atsm) demonstrating beneficial outcomes on neuroinflammatory markers in vitro and in vivo. These findings suggest that copper(II) complexes could be harnessed as a new app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 111 publications
1
11
0
Order By: Relevance
“…AD Patient-Derived iBEC Exhibit an Inflammatory Response to TNFα and IFNγ Stimulation. Since our previous studies demonstrated antineuroinflammatory effects of Cu(btsc) complexes in various models of neurodegeneration, 42,48,49 here we hypothesized that novel metal (btsc) complexes can achieve similar effects in iBEC and aimed to evaluate the immunomodulatory activity of selected compounds in the established AD-patient-derived platform.…”
Section: ■ Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…AD Patient-Derived iBEC Exhibit an Inflammatory Response to TNFα and IFNγ Stimulation. Since our previous studies demonstrated antineuroinflammatory effects of Cu(btsc) complexes in various models of neurodegeneration, 42,48,49 here we hypothesized that novel metal (btsc) complexes can achieve similar effects in iBEC and aimed to evaluate the immunomodulatory activity of selected compounds in the established AD-patient-derived platform.…”
Section: ■ Resultsmentioning
confidence: 99%
“…CuL 1 Reverses the TNFα/IFNγ-Induced Neuroinflammatory Phenotype in AD iBEC. Given that Cu(btsc) have previously demonstrated robust antineuroinflammatory actions in preclinical models of neurodegeneration (microglia, astrocytes and neuronal in vitro cultures, and animal models), 42,48,49 we anticipated that compounds in our library could exert similar, potentially therapeutic effects. Based on compound chemistry, toxicity, cellular accumulation, and iBEC monolayer permeability, we selected Cu(ATSM), its control Ni(ATSM), and a group of five promising Cu compounds (CuL 1 , CuL 4 , CuL 6 , CuL 7 , and CuL 9 ) for their further assessment in our model.…”
Section: ■ Resultsmentioning
confidence: 99%
See 3 more Smart Citations